Math, asked by sudhakarsawant056, 6 months ago

x^2+2√2-6=0
how to solve this problem​

Answers

Answered by amishacares
0

Step-by-step explanation:

x^2+2√2x-6=0

x^2+3√2x-√2x-6=0

x(x+3√2)-√2(x+3√2)=0

(x-√2)(x+3√2)=0

Answered by Anonymous
3

I think your question is

find the root of this function f ( x ) = x² + 2√2x - 6

x^2+2√2-6=0 \\  \\ \odot \:  \bf \:  \: as \:  \: we \:  \: know \\  \\    : \longrightarrow x =  \frac{ - b \pm \sqrt{ {b}^{2} - 4ac } }{2a}  \\  \\  \natural \:  \bf \:  \: putting \:  \: values \:  \:  \\  \\  : \longrightarrow x =   \frac{ - 2 \sqrt{2} \pm \sqrt{ ({2 \sqrt{2}) }^{2}  - 4 \times 1 \times ( - 6)}  }{2 \times 1}  \\  \\  \\  : \longrightarrow x =    \frac{ - 2 \sqrt{2}  \pm \sqrt{32} }{2}  \\  \\  \\ \underline {\bigstar \:  \:  \: { \bf  : \longrightarrow  x =   \sqrt{2}   }  \:  \:  \:  \: \bigstar  }

Similar questions